"RECHTSVERWERKING" DAN PENGADOPSIANNYA DALAM HUKUM TANAH NASIONAL - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2007)
Rechtsverwerking is a principle in Agrarian Law which states that owner of a land that leaves their land abandoned in certain period of time and lets other people to occupy and take advantage will cause the original owner to lose their rights of the land. This principle has been adapted to our national agrarian law thus becomes a part of Indonesian positive law however in law enforcement inside the court this principle tends to be deserted therefore creates an uncertainty in law and unfairness to people who have occupied a land in a long period of time.